Influence of Organizational Stressors among Executives in the Bank of Ceylon – Sri Lanka - Prabaharan, T. (University of Jaffna, 2018)
Stress is a serious and enduring problem in the workplaces. The last few decades have brought about dramatic changes like work in organizations. The demands for skilled or multi-skilled employees have increased in tandem with the growth of information technology. Employees are asked to perform multiple tasks and are forced to carry work home. All these changes in the work atmosphere, along with organizational changes, increased the organizational stress and related disorders among the employees. Therefore, banks should be conscious of the factors of organizational stressor affecting on role overload. This paper aimed to investigate the Influence of organizational Stressors on role overload among executives in the bank of Ceylon – Sri Lanka. The objective is to identify the level and impact of organizational Stressors on role overload. The data were collected from the respondents who are working as executives in Bank of Ceylon, Sri Lanka. The relevant data on various aspects have been collected using the questionnaire. Totally four hundred and three Executives were approached for data collection. The descriptive statistics and regression analysis were used to analyze the data. The results revealed that organizational Stress was significantly impacted on role overload. Therefore, it is reasonable to conclude that Banking Sector could design and offer stress reduction program to assist employees in reducing worry and anxiety, and cope with their stress and may further give them good advice when wanted. It may create a sound psychological wellbeing of the respondents
Keywords: organizational stressors; role overload; bank of ceylon.